Capital budgeting decision practice Indonesian companies : a case study of Sriwidjaya Fertilizer Company Limited (PT.Pusri) - Taufik; Gupta, Joyti; Ramachandran, Neelakantan; Swierczek, F.W.; The Government of Austria (Bangkok : Asian Institute of Technology, 1998)
The final purpose of the study is to know how to practice decision making in the capital budgeting. The most important thing that must be considered in making capital budgeting decision is selecting the finest investment which maximize the value of the firm because the capital budgeting decision which is taken will determine the long term profitability and the growth perspective of the firm itself. The Sriwidjaya Fertilizer Factory Limited, (PT. Pusri) is a company which is based on my research study. The company is located in Palembang, Indonesia. PT. Pusri established a new project for expansion which is called Pusri IB plant. The study will analyze whither the project will maximize the value of the firm or not. The calculation of cash flows of the project uses Discounted Cash Flow analysis. To observe the effect of various parameters on Discounted Cash Flow, the sensitivity analysis will be used
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1998
Keywords: Capital budget -- Indonesia; Capital budget -- Decision making